PROFIL PELAKSANAAN DAN HAMBATAN PRAKTIKUM PADA PEMBELAJARAN BIOLOGI KELAS XI DI SMA/SEDERAJAT SE-KECAMATAN KAMPAR TIMUR - Suryanti, Suryanti; Arnentis, Arnentis; Darmawati, Darmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to determine the implementation and practical barriers in learning biology class XI in SMA/equivalent in the eastern kampar district conducted in April to June 2017. The sample in this study as many as 113 students of class XI in high school / equivalent as Kampar Sub-district in the school year 2016/2017 and 5 class XI biology teachers as supporting data. The parameters of this research are implementation and practicum barriers to biology learning. The research instrument used questionnaire and observation sheet. The questionnaire consists of two parts: a closed questionnaire and an open questionnaire for data on the practicum implementation. The observation sheet is used for practicum data barriers. The data that has been collected is analyzed descriptively. The result of data analysis shows that the practicum implementation on all indicators is quite good with the average of 3.21 while the practicum barrier on the completeness of facilities and infrastructure is incomplete with the average of 1.48 in SMA/equivalent in the eastern kampar district.Keywords: Implementation And Practical Barriers